Ang mga Isyu at Interes sa Pagpangalan sa UP College of Business Administration na Cesar E. A. Virata School of Business - Taguiwalo, Judy M.; Navarro, Nelson A.; Tadem, Eduardo T.; Mendoza Jr., Amado (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Proceedings of the first "Marcos Pa Rin!" forum.